Picture this : World War I posters and visual culture - James, Pearl (Lincoln : University of Nebraska Press, 2009)
"The First World War was waged through the participation not just of soldiers but of men, women, and children on the home front. Mass-produced, full-color, large-format war posters were both a sign and an instrument of this historic shift in warfare. War posters celebrated, in both their form and content, the modernity of the conflict. They also reached an enormous international audience through their prominent display and continual reproduction in pamphlets and magazines in every combatant nation, uniting diverse populations as viewers of the same image and bringing them closer, in an imaginary and powerful way, to the war. Most war posters were aimed particularly at civilian populations. Posters nationalized, mobilized, and modernized those populations, thereby influencing how they viewed themselves and their activities. The home-front life -- factory work, agricultural work, domestic work, the consumption and conservation of goods, as well as various forms of leisure -- became, through the viewing of posters, emblematic of national identity and of each citizen's place within the collective effort to win the war. Essays by Jay Winter, Jeffrey T. Schnapp, Jennifer D. Keene, and others reveal the centrality of visual media, particularly the poster, within the specific national contexts of Britain, France, Germany, Russia, and the United States during World War I. Ultimately, posters were not merely representations of popular understanding of the war, but instruments influencing the reach, meaning, and memory of the war in subtle and pervasive ways"--Provided by publisher.
Introduction: Reading World War I posters / Pearl James -- Imaginings of war : posters and the shadow of the lost generation / Jay Winter -- War poster campaigns and images, comparative readings -- Barbaric anti-modernism : representations of the "Hun" in Britain, North America, Australia, and beyond / Nicoletta F. Gullace -- Chivalrous knights versus iron warriors : representations of the battle of materiel and slaughter in Britain and Germany, 1914-1940 / Stefan Goebel -- Regression versus progression : fundamental differences in German and American posters of the First World War / Jakub Kazecki and Jason Lieblang -- Envisioning the nation and imagining national aesthetics -- Young blood : Parisian schoolgirls' transformation of France's Great War poster aesthetic / Mark Levitch -- Race and empire in French posters of the Great War / Richard S. Fogarty -- Images of racial pride : African American propaganda posters in the First World War / Jennifer D. Keene -- Segodniashnii Lubok : art, war, and national identity / Andrew M. Nedd -- Figuring the body in the context of war -- Images of femininity in American World War I posters / Pearl James -- Humanitarians and he-men : recruitment posters and the masculine ideal / Meg Albrinck -- Iconography of injury : encountering the wounded soldier's body in American poster art and photography of World War I / John M. Kinder -- Epilogue / Jeffrey T. Schnapp.
Includes bibliographical references (pages 377-381) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: World War, 1914-1918 -- Posters; War posters -- History -- 20th century; World War, 1914-1918 -- Art and the war; Visual communication -- History -- 20th century; Popular culture -- History -- 20th century; World War, 1914-1918 -- Social aspects; World War, 1914-1918 -- Propaganda; Guerre mondiale, 1914-1918 -- Affiches; Affiches de guerre -- Histoire -- 20e siècle.; Communication visuelle -- Histoire -- 20e siècle.; Culture populaire -- Histoire -- 20e siècle.; Guerre mondiale, 1914-1918 -- Aspect social; Guerre mondiale, 1914-1918 -- Propagande; HISTORY -- Military -- World War I; Popular culture; Propaganda; Social aspects; Visual communication; War posters; Erster Weltkrieg; Plakat; Visuelle Kommunikation; Semiotik; Affiches; Oorlogspropaganda; Eerste Wereldoorlog; Beeldcultuur; 1900-1999.; 1900-1999; dissertations; Art; History; Posters; Academic theses; Thèses et écrits académiques.